VD_FINDINFO Jug / 2017 / 406 vom 24. Juli 2017 - VD Tribunal cantonal (2017)
CONSTATATION DES FAITS, VOLDROIT PÉNAL, INFRACTION D'IMPORTANCE MINEURE, INTENTION, FIXATION DE LA PEINE, EXPULSIONDROIT PÉNAL | 106 CP, 139 CP, 172ter CP, 47 CP, 66a bis CP, 89 CP, 10 CPP (CH)